Disclosure of Sustainability Reports in Basic Materials and Energy Sector Companies - Meliana Surjati; Yanti Yanti (International Journal Labs, 2023)
The primary objective of this study was to investigate the interplay between profitability, size, age, and board diversity concerning the disclosure of sustainability reports within the basic material and energy sector of the Indonesia Stock Exchange (IDX). To achieve this, the research employed the purposive sampling technique. The study focused on 20 companies operating within the basic material and energy sector, analyzing data spanning from 2019 to 2021. In total, 60 datasets were meticulously processed using the widely recognized SPSS software. Upon analyzing the data, a noteworthy pattern emerged. Specifically, the study revealed a statistically significant positive relationship between profitability and the extent of sustainability report disclosure. Contrary to expectations, the research findings did not establish any substantial influence stemming from firm size, company age, or board diversity on the level of sustainability reporting. In essence, while profitability appears to serve as a driving force behind increased sustainability report transparency, other factors such as firm size, age, and board diversity do not exhibit a discernible impact in this particular context.